Corporate wokeness: An expanding scope of CSR? - Farmaki, Anna (My University, 2022)
Despite the rise of woke capitalism, no attention has been paid by tourism scholars on corporate wokeness as an expanding scope of Corporate Social Responsibility (CSR). The aim of this paper is, thus, to introduce the concept of corporate wokeness in tourism scholarship and discuss the way it may be integrated within future CSR research. Specifically, the paper examines the meaning of corporate wokeness and compares and contrasts the concept to CSR in order to identify the commonalities and differences between the two. The potential effects that corporate wokeness may inflict on CSR are also discussed, with specific reference to the communication of corporate wokeness in tourism and hospitality. As such, this paper illuminates understanding of the practical implications the rise of corporate wokeness may carry and proposes an agenda for future research in order to advance knowledge on this topical issue.
Keywords: CSR; Wokeness; Tourism; Hospitality